Glycosylation site binding protein and protein disulfide isomerase are identical and essential for cell viability in yeast. - LaMantia, M (1991)
Glycosylation site binding protein (GSBP) has been shown to be identical to protein disulfide isomerase (PDI; EC 5.3.4.1) in a variety of multicellular organisms. We have utilized immunological and biochemical techniques to determine if GSBP and PDI are identical in yeast. Antiserum prepared against yeast GSBP identified in microsomes by its ability to be labeled with a peptide photoaffinity probe was found to recognize PDI purified from yeast. Moreover, this purified yeast PDI was found to be specifically labeled by the photoaffinity probe originally used to identify GSBP in a variety of eukaryotes. On the basis of these observations, we conclude that yeast GSBP and PDI are the same protein. The structure of the yeast PDI gene revealed a product with sequence similarity to higher eukaryotic PDI/GSBP. Disruption of this gene in yeast resulted in a recessive lethal mutation, indicating that PDI/GSBP is required for cell viability.